Human osteoarthritic synovial fluid increases excitability of mouse dorsal root ganglion sensory neurons: an in-vitro translational model to study arthritic pain. (13th August 2019) - Chakrabarti, Sampurna; Jadon, Deepak R; Bulmer, David C; Smith, Ewan St. John
Abstract: Objectives: Knee OA is a leading global cause of morbidity. This study investigates the effects of knee SF from patients with OA on the activity of dorsal root ganglion sensory neurons that innervate the knee (knee neurons) as a novel translational model of disease-mediated nociception in human OA. Methods: Dissociated cultures of mouse knee neurons were incubated overnight or acutely stimulated with OA-SF ( n = 4) and fluid from healthy donors ( n = 3, Ctrl-SF). Electrophysiology and Ca 2+ -imaging determined changes in electrical excitability and transient receptor potential channel function, respectively. Results: Incubation with OA-SF induced knee neuron hyperexcitability compared to Ctrl-SF: the resting membrane potential significantly increased (F(2, 92) = 5.6, P = 0.005, ANOVA) and the action potential threshold decreased (F(2, 92) = 8.8, P = 0.0003, ANOVA); TRPV1 (F(2, 445) = 3.7, P = 0.02) and TRPM8 (F(2, 174) = 11.1, P < 0.0001, ANOVA) channel activity also increased. Acute application of Ctrl-SF and OA-SF increased intracellular Ca 2+ concentration via intra- and extracellular Ca 2+ sources. Conclusion: Human OA-SF acutely activated knee neurons and induced hyperexcitability indicating that mediators present in OA-SF stimulate sensory nerve activity and thereby give rise to knee pain. Taken together, this study provides proof-of-concept for a new method to study the ability of mediators present in joints of patients with arthritis to stimulate nociceptor activity and hence identify clinically relevant drug targets for treating knee pain.